Introduction to the Thematic Issue - Večerník, Jiří (Sociologický časopis, 2019)
In sociology, social stratification is an evergreen field. It is moreover a field that itself embraces a vast and expanding range of interests relating to occupational and educational structures, earnings and household income, objective and subjective well-being, poverty, and exclusion and inclusion. It is an area of research that invites us to compare various forms and dimensions of inequality across countries and regions. This issue of the Czech Sociological Review deals with several comparative and innovative aspects of social stratification in Central Europe. As regards sources of data on this subject, there is no recent sociological survey on social stratification in Europe available at present-the last one we can draw on is the ISSP module on Social Inequality from 2009, which was conducted on small samples, while data from the one just fielded in 2019 are not yet available. The regular biannual waves of the European Social Survey (ESS), conducted since 2002 on somewhat bigger samples, are certainly also useful for studying basic aspects of social stratification and mobility, but the topic of social stratification itself has not yet been the specific focus of any wave of the ESS so far. However, one inviting opportunity exists, which is to mine the European Union Statistics on Income and Living Conditions (EU-SILC). Since 2005 the EUSILC has been producing comparative cross-sectional and longitudinal datasets on household income, living conditions, and poverty, as well as on key status variables such as occupation, education, and earnings. Its special advantage is that both personal and household perspectives can be applied. Another data source is the European Union Labour Force Survey (EU-LFS), available since 2004. This thematic issue assembles a series of prevailingly comparative empirical contributions that are based mainly on statistical sources and ISSP data and focus on the post-communist region of Central-East Europe and specifically the Czech Republic, Hungary, Poland, and Slovakia (Visegrád Four - V4). The V4 countries are often regarded as a single homogeneous region, though-as the reader will see-they differ considerably in terms of their social structures and trends. Where possible, Austria is added for comparison, as it represents the nearest benchmark country that is linked to the V4 by historical roots but fortunately escaped Soviet rule.